The Use Of The Black Scholes Model In Determining The Price Of The European Type Option - Simarmata, Justin Eduardo; Ahzan, Z.N. (Journal of Research in Mathematics Trends and Technology, 2021)
An option is a contract between the seller’s option and the buyer’s option, while the factors that affect the value of the option are the stock price (S), the strike price (K), the maturity date (T), interest rate (r), volatility (Ïƒ). The application of the models in this study uses daily stock closing data from PT PP London Sumatra Indonesia Tbk from July 18, 2019, until September 19, 2019, so that the initial stock price is = Rp1,090, the interest rate is 5.5%, the value stock price volatility is 0.253. The computation of the option prices using the Black Scholes model aims to found out all the values generated from European type put options. By applying the Black Scholes model, the value generated from the European type option is Rp14,768.